Strategi Pelayanan Prima di Kantor Perpustakaan Arsip dan Dokumentasi Kabupaten Pesisir Selatan - Sari, Maiyas Sandra; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of writing this article are: (1) describe how the strategy of excellent service in the Office of Libraries, Archives, and Documentation Kabupaten Pesisir Selatan, (2) describe any obstacles countered in achieving excellent service in he Office of Libraries, Archives, and Documentation of Kabupaten Pesisir Selatan. The method use disqualitative approach. Collection of data through observation, interviews, and library research. Observations directly to the Office of Libraries, Archives, and Documentation of Kabupaten Pesisir Selatan. Based on analyzing the data can be summarized as follows. (1) strategies to realize excellent service in the Office of Libraries, Archives, and Documentation of Kabupaten Pesisir Selatan of identifying primary determination of quality service, manage ekspentasi customers, managing service quality evidence, educating consumers about the services, fostera culture of quality, follow up services, and develop information systems quality of service, (2) the constraints faced in the Office of Libraries, Archives, and Documentation in the Kabupaten Pesisir Selatan realization excellent service strategy that is not the realization of automating quality. Keywords: excellent service; excellent service strategy Â